El precio de la vivienda en Espa\~na tras el inicio de la crisis económica: Un análisis empírico; Housing prices in Spain after the beginning of the financial crisis: An empirical analysis - Jonathan Torres-Tellez; Alberto Montero Soler (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– The objective of this research is to analyse the factors that have influenced on housing market in Spain after the beginning of the financial crisis. To this end, this investigation has used a fixed effect data panel covering from 2008 to 2016 for 17 Spanish regions, which has taken into consideration supply and demand variables. Our findings suggest that demand is still the main price driver for the Spanish case. In addition, supply keeps pushing prices up, a symptom that may show the possible existence of a housing bubble.
Keywords: R21; R31; 330; housing market; housing prices; panel data; Spain